Resiliensi dan Kerentanan: Mata Pencarian Dayak Bakumpai di Tengah Ekspansi Perkebunan Kelapa Sawit di Kabupaten Barito Kuala - Rochgiyanti Rochgiyanti; Rahmat Nur; Nasrullah Nasrullah; Lumban Arofah; Fathurrahman Fathurrahman; Sigit Ruswinarsih; Alfisyah Alfisyah; Yuli Apriati; Cucu Widaty; Sumiati Sumiati; Syahlan Mattiro; Muhammad Adhitya Hidayat Putra; Anggaunitakiranantika Anggaunitakiranantika (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2026)
The expansion of large-scale oil palm plantations in South Kalimantan has triggered massive transformations in the ecological landscape and the socioeconomic structure of local communities. This study aims to analyze the dynamics of resilience and vulnerability in the livelihoods of the Dayak Bakumpai people, a Dayak sub-ethnic group with a strong historical dependence on river and wetland ecosystems. Using qualitative methods with a case study approach, data were collected through participatory observation, in-depth interviews, and document analysis. The findings indicate that land conversion into oil palm plantations has eroded the community’s traditional resource base, such as reduced access to forest land and the loss of local biodiversity. These conditions create new vulnerabilities, particularly for households lacking the capital to adapt to the market economy. However, on the other hand, forms of resilience were identified, including ecological resilience and adaptive land management, economic resilience and food sovereignty, socio-cultural resilience (social capital), as well as institutional resilience and litigation.  This study concludes that although the Dayak Bakumpai community demonstrates a certain degree of resilience, the ongoing pressure of monoculture expansion without strong protection of customary rights risks triggering deeper structural marginalization in the future.